Analysis of heavy metals in the conversion of lake sediment and restaurant waste by black soldier fly (Hermetia illucens) - Hu, Caixi; Yang, Longyuan; Wang, Hanlin; Xiao, Xiaopeng; Wang, Zhongwen; Gong, Xiangyi; Liu, Xianli; Li, Wu (Frontiers in Bioengineering and Biotechnology, 2023)
The risk posed by heavy metals makes it difficult to dispose of sediment contaminants from dredging lakes in China. Black soldier fly (Hermetia illucens) can convert organic waste, such as restaurant waste and lake sediment, to high-value-added protein feed and fertilizer. Few experimental groups were formed in the current study to explore the black soldier fly larvae (BSFL) conversion of heavy metals present in the sediment. The results demonstrated that BSFL could survive in pure sediment with an 84.76% survival rate. Relative to the substrate, BSFL could accumulate 70–90% zinc (Zn), chromium (Cr), copper (Cu), and 20–40% cadmium (Cd) and lead (Pb). The experimental group 2:3, with 40% lake sediment and 60% restaurant waste, was the best group after conversion for 15 days, which showed a 95.24% survival rate of BFSL, 82.20 mg average weight of BFSL, 8.92 mm average length of BFSL, with varying content of heavy metals such as Cu (43.22 mg/kg ), Zn (193.31 mg/kg), Cd(1.58 mg/kg), Cr (25.30 mg/kg) Cr, and Pb (38.59 mg/kg) in BSFL. Furthermore, the conversion residue conforms to the relevant standards of organic fertilizer in China and can be used as organic fertilizer. Overall, the present study shows that black soldier flies can improve the resource utilization of lake sediment, especially by reducing the effect of heavy metals.